PSYCHOLOGICAL DETERMINANTS OF DIGITAL ADDICTION: AN ANALYTICAL AND CONCEPTUAL STUDY - Zayniddinova , Mukhlisa (Effective scientific journals, 2026)
Digital addiction has become a critical psychological and social issue in the contemporary digital era. The pervasive use of smartphones, social media platforms, and online environments has significantly altered patterns of behavior, emotional regulation, and social interaction. This study aims to examine the psychological determinants of digital addiction through a systematic conceptual and analytical approach. Drawing on contemporary psychological theories and empirical findings, the study identifies emotional distress, stress and anxiety, low self-esteem, impulsivity, and unmet social needs as key contributing factors. Analytical tables are used to synthesize existing evidence and highlight the psychological mechanisms underlying problematic digital use. The findings suggest that digital addiction should be conceptualized not merely as excessive technology use, but as a maladaptive coping strategy rooted in emotional regulation deficits. The study contributes to behavioral addiction theory and provides implications for psychological prevention and intervention.